The role of ACE inhibitor in reducing persistent proteinuria in nephrotic syndrome - Erika Hutabarat; Husein Alatas; Sri Rezeki Hadinegoro (Indonesian Pediatric Society, 2002)
Background Patients with persistent proteinuria are at risk for progression to end-stage renal failure. Angiotensin converting enzyme inhibitor (ACEI) can decrease proteinuria in nephrotic syndrome (NS) patients with persistent proteinuria.Objective To evaluate the effectiveness of ACEI (enalapril) in reducing proteinuria in NS.Methods This study was conducted as a randomized double blind clinical trial with crossover design on persistent proteinuria NS patients who visited Cipto Mangunkusumo Hospital from December 2000 until July 2001. Twenty patients were enrolled in this study. Ten patients received enalapril 10 mg/day for 8 weeks and ten patients received placebo. Angiotensin converting enzyme inhibitor as considered effective if proteinuria was reduced for at least 50%.Results The patients aged between 2-16 years with a mean of 11.3 years and consisted of 16 boys and 4 girls with a ratio of 4:1. Urine protein and creatinine ratio (Up/Uc) was used to evaluate proteinuria. In the ACEI group, the mean value of proteinuria increasedtrom5.6 (95%CI 1.1 ;2.2)to 6.7 (95%CI 0.3;13.2) (p=0.721),Â although it decreased in five patients. Decreased proteinuria to 50%or more was found in 2 out of 10 patients in the enalapril group while in the placebo group it was found in 3 out of 10, but this differences was not statistically significant (,0=0.5). Systolic blood pressure decreased significantly (p=0.0185) from 107 mmHg (95%CI 101.1;112.9 mmHg) to 103 mmHg (95%CI 96.2;109.8 mmHg) although still in nonnal range.Conclusions The efficacy of enalapril in reducing proteinuria could not be evaluated yet. A further study with greater sample and longer observation is needed.